2017
DOI: 10.1111/tbed.12721
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of porcine circovirus type 2 infection reveals a novel genotype PCV2f

Abstract: Porcine postweaning multisystemic wasting syndrome (PMWS) caused by porcine circovirus type 2 (PCV2) is a disease causing severe economic losses annually worldwide to the pig industry. PCV2 infection was first reported in China in 2000, and currently has three major genotypes, PCV2a, b and d, circulating in this country. To further elucidate the origin and prevalence of PCV2 in China, 123 clinical pig tissue samples collected in 25 provinces between 1990 and 1999 were analysed by PCV2-specific PCR, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 39 publications
1
52
0
1
Order By: Relevance
“…A retrospective analysis of PCV2 infection in China has also been performed with the same clinical samples of the present PCV3 study, with the earliest PCV2 case also being detected in 1996 (Bao et al., ). In the latter report, PCV2a and a novel genotype PCV2f were found circulating between 1996 and 1999 in China, with PCV2a dominant (20/23) (Bao et al., ).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…A retrospective analysis of PCV2 infection in China has also been performed with the same clinical samples of the present PCV3 study, with the earliest PCV2 case also being detected in 1996 (Bao et al., ). In the latter report, PCV2a and a novel genotype PCV2f were found circulating between 1996 and 1999 in China, with PCV2a dominant (20/23) (Bao et al., ).…”
Section: Resultsmentioning
confidence: 86%
“…A retrospective analysis of PCV2 infection in China has also been performed with the same clinical samples of the present PCV3 study, with the earliest PCV2 case also being detected in 1996 (Bao et al., ). In the latter report, PCV2a and a novel genotype PCV2f were found circulating between 1996 and 1999 in China, with PCV2a dominant (20/23) (Bao et al., ). Previous studies revealed that PCV2a was the earliest genotype of PCV2, with the time to the most recent common ancestor (TMRCA) estimated to be 1964 (1948–1974) (Franzo, Cortey, Segalés, Hughes, & Drigo, ) or 1966 (1945–1983) (Firth, Charleston, Duffy, Shapiro, & Holmes, ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…For example, the recombinant cluster that recombines between PCV2a and PCV2b strains can occur in the Cap protein-coding region through different patterns and yield different recombinants [16]. In 2018, results from a retrospective analysis showed that a new genotype, PCV2f, was tracked to samples collected in 1996 in China [17]. Up to now, there is no specific treatment available for PCV2 infection and PCVADs.…”
Section: Introductionmentioning
confidence: 99%